Corporate Website Job Recruitment Platform: A Moderated Mediation Model of Organisational Image - David Yoon Kin Tong; Xue Fa Tong; Shiwen Luo (Asian Academy of Management Journal, 2022)
Corporate companies’ websites recruitment in advanced countries is well established. However, lesser is known about the Malaysian students and employed jobseekers’ intention to apply for jobs on the corporate companies’ websites. Therefore, this study aims to assess the subjective perceptions of these two groups’ intentions to apply for jobs on the websites. This study also aims to analyse the mediating effect of organisational image on perceived person-job fit (P-J fit) and perceived website usability (PWSU) which may be moderated by these two groups of jobseekers’ intentions. The conceptual model was first analysed using two-level confirmatory factor analysis. Adopting Hayes’ Model 7 template, AMOS software was used to differentiate the two groups’ perceptions. The results indicate that the perceived P-J fit and PWSU are the main factors influencing jobseekers’ intentions to apply for jobs on corporate websites. The moderated mediation technique has identified an indirect effect between perceived P-J fit and the intention to apply for jobs indicating the importance of established organisational image that it arouses applicants’ pursuit intention. Thus, the corporate human resource managers need to ensure the sites are designed for easy navigation and job advertisements that contain updated job information and realistic job preview. Using this platform, companies can reduce costs and time for the recruitment of talents. This study provides the subjective perceptions of jobseekers’ intention study and it contributes to the first component of Planning Theory of Intention. Lastly, this research also contributed to an alternate research method of analysing the moderated mediation using AMOS.